GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 1496 species occurrences available in GBIF matching the query: TaxonKey: Selaginella kraussiana (Kunze) A. Braun. The dataset includes 1496 records from 101 constituent datasets: 1 records from National Biodiversity Data Bank. Observation records, 1900-2014. 1 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 5 records from OEH Atlas of NSW Wildlife. 194 records from Botanical Society of the British Isles - Vascular Plants Database. 1 records from HUEM - Herbário da Universidade Estadual de Maringá. 9 records from Phanerogamic Botanical Collections (S). 27 records from PRECIS (KwaZulu-Natal Herbarium). 4 records from GRBGT: Southern Cape Herbarium Specimen Collections (1882-2008). 121 records from Naturalis Biodiversity Center (NL) - Botany. 185 records from PRECIS. 1 records from SPF - Herbário da Universidade de São Paulo. 1 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 6 records from SANT herbarium vascular plants collection. 1 records from UFP - Herbário UFP - Geraldo Mariz. 4 records from Species data extracted from the National Vegetation Database. 4 records from IICT Herbário LISC. 3 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 1 records from SA Flora (BDBSA). 2 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 12 records from Phytochorologie des départements français. 3 records from CESJ - Herbário Leopoldo Krieger. 7 records from Irish Vascular Plant Data - Paul Green. 1 records from MBM - Herbário do Museu Botânico Municipal. 1 records from OHN. 1 records from FCAB - Herbário Friburguense. 2 records from Merseyside BioBank - North Merseyside Other Taxa (verified). 4 records from Herbarium of the Université Libre de Bruxelles. 81 records from Australia's Virtual Herbarium. 17 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 1 records from Natural History Museum Maastricht (NL) - Herbarium. 11 records from Consortium of California Herbaria. 65 records from iNaturalist Research-grade Observations. 1 records from UCBG TAPIR Provider. 6 records from CONN. 1 records from University of California Museum of Paleontology. 5 records from NMNH occurrence DwC-A. 9 records from OAC-BIO Herbarium. 5 records from Herbario de la Universidad de Granada: GDA. 8 records from The Flora of County Wexford. 6 records from INPN - Données flore des CBN agrégées par la FCBN. 2 records from ASE - Herbário da Universidade Federal de Sergipe. 1 records from UEC - Herbário da Universidade Estadual de Campinas. 5 records from Jardin botanique de Montréal (JBM). 2 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 13 records from BSBI tetrad data for Ireland. 30 records from Tropicos Specimen Data. 27 records from Natural History Museum (London) Collection Specimens. 4 records from Natural History Museum, Vienna - Herbarium W. 5 records from Flora-On: occurrence data of the flora of mainland Portugal. 8 records from Australian National Herbarium (CANB). 2 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 9 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 7 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 24 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 6 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 1 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 1 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 8 records from Aranzadi Zientzi Elkartea. 23 records from GBIF-PORTUGAL-Herbário João de Carvalho e Vasconcellos, I.S.A./U.T.L.. 2 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 3 records from Herbario de la Universidad de Sevilla. 1 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 5 records from California State University, Chico. 2 records from UCD BOTANICAL CONSERVATORY. 22 records from NSW herbarium collection. 5 records from Herbarium Berolinense. 64 records from Botanical Society of the British Isles - Vascular Plants Database additions since 2000. 1 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 5 records from Herbarium of Namur. 6 records from Herbarium of Umeå University (UME). 45 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 8 records from Jardín Botánico Atlántico, Gijón: JBAG-Laínz. 5 records from University of Ghana - Ghana Herbarium. 100 records from Precis Plant Data. 5 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 2 records from Lund Botanical Museum (LD). 5 records from Irish vascular plant data 1999-2009. 1 records from SBT-Living. 14 records from Bernice P. Bishop Museum. 3 records from Carnet en Ligne. 8 records from The Flora of County Wexford. 10 records from Botany (UPS). 1 records from crsn_data. 2 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 8 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 54 records from New Zealand Biodiversity Recording Network. 16 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 22 records from SysTax - Botanical Gardens. 2 records from Vascular Plant Herbarium, Oslo (O). 1 records from E. C. Smith Herbarium (ACAD). 17 records from The Flora of County Waterford. 4 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 10 records from BHCB-SL - Herbário UFMG - Samambaias e Licófitas. 11 records from Instituto de Botánica Darwinion. 1 records from Northern Ireland Environment Agency - EHS Species Datasets. 12 records from Herbarium WRSL, Main Collection. 3 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 3 records from CAS Botany (BOT). 2 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 3 records from SJRP-Pteridophyta - Herbário de Pteridophyta de São José do Rio Preto. 6 records from PACA-AGP - Herbarium Anchieta.
Keywords: GBIF; biodiversity; species occurrences